The Resilience of Madurese Santri in Facing Modernity: A Study of the Indonesian Ngabuleh Tradition - Ali Sodiqin; Nur Komala (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2022)
This article explores the survival strategy of the Madurese Santri in maintaining local traditions in the middle of the incessant currents of modernity. The Ngabuleh tradition that has been institutionalized in the Pamekasan Madurese society is a portrait of how the Madurese Santri experienced the technological advances that affect people’s behavior, especially young people. This tradition serves as a medium for preparing santri who will marry by serving in the Kyai’s residence. This enables them to learn how to prepare the household. Furthermore, the goal is that when they get married, they will be fully ready to settle down physically and mentally. This study uses Bronislaw Malinowski’s structural functionalism theory by placing the Ngabuleh tradition as an integral part of the social system. The persistence of the Ngabuleh tradition is a strategy for inheriting local traditions to the younger generation as well as a strategy for surviving the negative effects of globalization that penetrate regional boundaries to rural areas. Additionally, the Ngabuleh tradition is a way of showing the social identity of the Madurese santri, namely religiosity, integrity, loyalty or obedience, and autonomy. Ngabuleh serves as a strategy of cultural resilience as well as a form of obedience in maintaining and preserving local wisdom.